Detection of Escherichia coli heat-labile enterotoxin in cell cultures. - Paulino, Grace P. (1982)
A study which aims to establish base-line information on cultural conditions for optimal in-vitro production of LT and subsequent enterotoxin assay in cell cultures using local isolates of ETEC is hereby reported. The sensitivity of PS-EK cells in the detection of LT enterotoxin over Vero cells is likewise determined. A series of experiments involving manipulations of pH with varying intervals of incubation of cultures with BB-TSB or PB-TSB, as culture medium were done. Finally, LT was successfully extracted under optimal conditions such as: inoculating organisms at an initial density of 9 x 10(exponent of 8) organisms per ml. or the equivalent of McFarland number 3 in PB-TSB with an initial pH of 8.0 and 24 hours of incubation with shaking (200 rpm) at 35-37(degree centigrade). These conditions are known to favor LT production and not ST. All the 10 E. coli strains used were isolated from avians and were found enterotoxigenic by the piglet-ligated loop technic. Crude LT was prepared by clarifying the culture medium of bacteria by centrifugation (3000 rpm) at 4(degree centigrade). The supernate was filtered through millipore filter with pore size of 0.4 u and kept in the refrigerator, for a period not exceeding 1 week, until assayed. The crude LTs were assayed in triplicate tubes each of confluent monolayers of Vero and PS-EK cells. Tubes were washed twice with sterile Hanks' BSS prior to addition of 1.0 ml per tube of crude LT. Cells were observed for rounding-off at intervals of 2, 4, 6 and 8 hours. Vero and PS-EK cell culture assays of LT, produced and extracted from BB-TSB with initial pH of 7.8 after 8 hours of incubation, detected 2 out of 10 (20 ) and 3 out of 10 (30 ) ETEC, respectively, as LT producing strains. Furthermore, the number of ETEC detected as LT producing strains by Vero and PS-EK cell culture assays increased to 5 out of 10 (50 ) and 8 out of 10 (80 ), respectively, when the enterotoxins were produced and extracted from PB-TSB with initial pH of 8.0 after 24 hours of incubation. It was hypothesized that BB, although a better buffer than PB, was also inhibitory in the biosynthesis and release of LT across the bacterial cell walls.